1996
DOI: 10.2172/274146
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion in supercritical fluids

Abstract: Portions of this document may be illegible in electronic image products. Images are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…Since the static continuum model has a gradient-squared free energy, one would suspect that z = 2. Indeed, scaling with z = 2 has been seen numerically in simulations of the square lattice dimer model [18].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Since the static continuum model has a gradient-squared free energy, one would suspect that z = 2. Indeed, scaling with z = 2 has been seen numerically in simulations of the square lattice dimer model [18].…”
Section: Introductionmentioning
confidence: 85%
“…Ref. [18] simulated the random dimer model with dimer-flip dynamics; however rather than periodic boundary conditions, that work used "Aztec diamond" boundary conditions [11] such that h(r) is fixed (and spatially nonconstant) along the edges. The continuum equations below would still predict τ (L) ∼ L 2 in that geometry, as was observed in the simulations.…”
Section: B Dynamic Scalingmentioning
confidence: 99%
“…When free water exists in the pipeline, it will be saturated with CO 2 and the corrosion rate will be significant for carbon steel because of the formation of carbonic acid (H 2 CO 3 ). In addition, even though pure, dry CO 2 is not corrosive, there are several studies which provide qualitative evidence for corrosion on carbon steel in water-saturated supercritical CO 2 phase (Russick et al, 1996;Propp et al, 1996;McGrail et al, 2009). Thus, to be able to consider the corrosion risk in such pipelines, quantitative evaluation of corrosion in both CO 2 -saturated water and water-saturated CO 2 phases will be needed.…”
Section: Introductionmentioning
confidence: 99%
“…Roberson (1973, 1975) and West (1974) also confirmed that in the shortterm exposure to dry SC CO 2 the corrosion rate of carbon steel was zero. During 200-day experiments at 9-12 MPa and 160-180°C, the corrosion rate of AISI 1080 carbon steel was only in the order of 0.01 mm/year (Propp et al, 1996). A similar result was also observed during 12 years of pipeline service with high pressure dry CO 2 , and the corrosion rate of carbon steels encountered 0.5-2.5 μm/year (Gill, 1985;Newton Jr., 1984).…”
Section: Research Progress In the Field Of Sc Co 2 Corrosionmentioning
confidence: 66%